School Management in Forming Children's Religious Character - Sandiko, Sandiko; Faiz, Faiz; Rozi, Fathor; Wahyuni, Uun; Yulastari, Yulastari (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
Religious character education for children is essential to do from an early age to strengthen their character so that other people's negative behavior does not easily influence them. In its implementation, religious character education requires management to run optimally. This study aims to understand school management in shaping the religious character of children through gadget media which was carried out at RA Sunan Ampel, Probolinggo. This study uses a qualitative descriptive approach with the type of case study. The results showed that RA Sunan Ampel arranged a series of religious activities that were strengthened by school management through the stages of planning, regulating the implementation of activities, and regularly evaluating by utilizing gadgets through the digital application